Pendekatan Rule of Reason sebagai Cerminan Penafsiran Teleologis dalam Hukum Persaingan Usaha di Indonesia - Ngabut, Rupertus Arvinci; Silalahi, Wilma (Journal of Business, Management, and Social Studies, 2025)
This study examines the convergence between the Rule of Reason approach and teleological interpretation in the enforcement of Indonesian competition law, particularly in cartel cases. Using a normative doctrinal methodology, the paper explores how substantive economic assessments align with purposive readings of legal norms. Despite the seemingly formalistic wording of Article 5 and 11 of Law No. 5 of 1999, this study finds that the Indonesian Competition Commission (KPPU) has increasingly adopted an effect-based analysis in cartel decisions. This shift suggests a move toward teleological interpretation that emphasizes legal purpose and economic rationale. The research contributes to the refinement of interpretive theory in Indonesian competition law and offers practical insights for enhancing regulatory consistency and adaptive law enforcement.